2003
DOI: 10.1046/j.1461-9563.2003.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile semiochemical impact on trapping and distribution in maize of northern and western corn rootworm beetles (Coleoptera: Chrysomelidae)

Abstract: 1 Field studies evaluated plant attractants and analogues as tools to move corn rootworm beetles (Diabrotica spp.) into areas to be treated with toxic baits for population suppression via mass removal/annihilation of reproductive adults. 2 When dispensed from sticky traps in maize, 2-phenyl-1-ethylamine and 2-phenyl-1-ethanol captured more northern corn rootworm, Diabrotica barberi, than did 4-methoxyphenethanol. Only 2-phenyl-1-ethanol attracted the western corn rootworm, Diabrotica virgifera virgifera, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…However, they also hint that semiochemicals can be effective depending on the developmental stage of the crop. Similar work by Hammack () shows that kairomones are effective if used at the right period of the crop phenology. Therefore, the unripe stage of fruit development would be the ideal period to use oviposition attractants and reduce the pest population by preventing oviposition.…”
Section: Discussionmentioning
confidence: 97%
“…However, they also hint that semiochemicals can be effective depending on the developmental stage of the crop. Similar work by Hammack () shows that kairomones are effective if used at the right period of the crop phenology. Therefore, the unripe stage of fruit development would be the ideal period to use oviposition attractants and reduce the pest population by preventing oviposition.…”
Section: Discussionmentioning
confidence: 97%
“…Blend 2 showed much higher catches than did ( E )‐2‐hexenal, possibly due to the synergistic effect of components in blend 2. Some studies confirmed that the attractiveness of semiochemical mixtures are stronger than those of single components (Zhang et al , 1999; Hammack, 2003; Blackmer et al , 2004; Leskey et al , 2005; Pinero et al , 2006). One of our objectives in the current study was to determine attractiveness of individual and various blends of compounds found in host plants.…”
Section: Discussionmentioning
confidence: 92%
“…2 and 3; Tables 1 and 2), the volatiles played an important role in selecting host plants. As abovementioned, fungi may induce the changes of plant volatiles so that insects are affected (Hammack, 2003). For instance, healthy Melaleuca quinquenervia leaves attracted more female Oxyops vitiosa weevils in olfactory bioassays when compared to the leaves infected with rust Puccinia psidii (Rayamajhi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%